Production of polyhydroxybutyrate (PHB) from bacillus cereus by using sawdust as a substrate - Farizah, Hamid (2010)
The objectives of this research are to determine the production of lignin degradation in sawdust using Bacillus cereus and to study the potential of Bacillus cereus for PHB production using sawdust as a substrate. There consist of two major parts which are fermentation for delignification of sawdust and production of PHB. For delignification analysis, Klason method is used in order to determine the percentage of lignin content and lignin degrades by using sawdust as a substrate. Bacillus cereus act to degrade lignin in the sample. Based on the experiment sample 1 shows the lower percent of lignin content with 38.45% and become the higher percentage of lignin degrade with 13.75%. This is because the bacteria which are Bacillus cereus break down the long carbohydrate chains or hemicellulose converted the sawdust into short chains of glucose and eventually individual glucose. While sample 4 shows the lowest percentage of lignin degrade but higher percentage of lignin content. The second part is on the production of PHB. From the result, percentage yield of PHB produced from cellulose and glucose are 1.29% and 3.42%. In conclusion, Bacillus cereus has potential to produce PHB using sawdust as a substrate although the yield is smaller. Several precautions must take placed to avoid any mistaken during the experiment. As a recommendation HPLC can be used to obtain more accurate result.